Burkitt's lymphoma in a young boy progressing to systemic lupus erythematosus during follow-up: a case report and literature review - Chenxi Liu; Ci Pan; Yingying Jin; Hua Huang; Fei Ding; Xuemei Xu; Shengfang Bao; Xiqiong Han; Yanliang Jin (Frontiers Media S.A., 2024)
IntroductionPatients with systemic lupus erythematosus (SLE) are at a higher risk of developing cancer, particularly hematological malignancies such as lymphoma and leukemia. However, existing studies on this topic that assess cancer incidence following SLE diagnosis are limited. In addition, SLE can be diagnosed after cancer, although such cases in children have been rarely reported.Case reportWe present the case of a 2.6-year-old boy who presented to our institute with fever and abdominal pain. His physical examination revealed a periumbilical mass, which was pathologically diagnosed as Burkitt's lymphoma. Autologous stem cell transplantation was performed to consolidate the effect of chemotherapy and reduce the risk of cancer relapse. He was diagnosed with SLE 5 years later, following the presentation of a fever with rash, positive autoantibodies, decreased complement, and kidney involvement. At the final follow-up, the patient was still alive and showed no recurrence of Burkitt's lymphoma or disease activity of SLE.ConclusionDespite the low frequency of SLE in children with lymphoma, cancer and SLE may be induced by a common mechanism involving B-cell cloning and proliferation. Therefore, hematologists and rheumatologists should be aware of the occurrence of these two conditions during patient follow-up.